PENGARUH PEMBERIAN LARUTAN SARI KURMA (PHOENIX DACTYLIFERA L.) DAN LARUTAN FLUOR TERHADAP KEKERASAN EMAIL GIGI SETELAH DIRENDAM DALAM MINUMAN RINGAN BERKARBONASI - Mety Dwi Putri Eszy; Afriwardi Afriwardi; Susi Susi (Andalas Dental Journal, 2014)
Soft drink with low pH (5,5) causes tooth erosion. Erosion may result in a decrease in surface hardness of tooth enamel. This research will be used a solution of palm juice and solution of fluoride to increase the surface hardness of tooth enamel. The purpose of this study was to evaluate effect of using a solution of palm juice 100%, 75%, 50%, 25% and APF 1,23% to the surface hardness of tooth enamel. The methode used in this research is the experimental laboratory and were tested for their hardness using Vicker Hardness Tester.Measurement performed three times, initial hardness, after all specimens was soaked in soft drink for 25 hours and were then applied with 100%, 75%, 50%, 25% solution of palm juice dan APF 1,23%. Data was analyzed by using SPSS with Repeated ANOVA.The result showed that a significant decrease in tooth enamel hardness on immersion in carbonated soft drink (p<0,05) and increased hardness of surface enamel after application with 100% solution of palm juice with a mean increase of microhardness 42,91VHN, 38,46 VHN with 75% solution of palm juice, 35,836 VHN with 50% solution of palm juice,29,41 VHN with 25% solution of palm juice dan 23,94 VHN in APF 1,23%.The result of this study is there is no significant difference enamel hardness after applied with 100%, 75%, 50%, 25% solution of palm juice and APF 1,23%.